Aggressive locoregional management of recurrent peritoneal sarcomatosis. Issue 4 (5th February 2013) - Baumgartner, Joel M.; Ahrendt, Steven A.; Pingpank, James F.; Holtzman, Matthew P.; Ramalingam, Lekshmi; Jones, Heather L.; Zureikat, Amer H.; Zeh, Herbert J.; Bartlett, David L.; Choudry, Haroon A.
Abstract Background and Objectives Peritoneal sarcomatosis responds poorly to systemic chemotherapy and demonstrates high rates of recurrence after resection. We sought to determine perioperative and oncologic outcomes after cytoreductive surgery (CRS) and hyperthermic intraperitoneal chemoperfusion (HIPEC) for recurrent sarcomatosis. Methods We reviewed 15 patients undergoing 17 CRS/HIPEC for recurrent sarcomatosis from a prospective database. Results There were four synovial cell sarcomas, five liposarcomas, three leiomyosarcomas, two gastrointestinal stromal tumors (GIST), and three other sarcomas. Adequate cytoreduction (CC‐0/1) was achieved in all patients, with a median intra‐operative Simplified Peritoneal Carcinomatosis Index of 6 (range: 3–9). Median blood loss and operative time were 1 L (range: 450–5, 200) and 402 min (range: 324–680), respectively. Chemoperfusion drug was mitomycin C, cisplatin, or doxorubicin. Significant post‐operative complications (Clavien–Dindo III/IV) occurred in four (24%) patients, with no 60‐day mortalities and three (18%) 60‐day re‐admissions. Median intra‐abdominal disease‐free and overall survival after CRS/HIPEC was 17.2 (95% CI: 2.4–19.7 months) and 22.6 months (95% CI: 6.1–62.6 months), respectively. There was a trend towards delayed recurrence after combined CRS/HIPEC than after prior CRS alone (17.2 months vs. 10.7 months, respectively; P = 0.52). Conclusion Cytoreduction combined with HIPEC may improve loco‐regional disease control in patients with recurrent sarcomatosis. J. Surg. Oncol. 2013;107:329–334. © 2013 Wiley Periodicals, Inc.